2019
DOI: 10.1016/j.bjorl.2018.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic approach to pediatric acute mastoiditis – an update

Abstract: The main points of the management protocol are: initiate a broad-spectrum intravenous antibiotic treatment; mastoidectomy should be performed if the infection fails to be controlled after 48h of administering intravenous antibiotic therapy. We believe that early mastoidectomy prevents serious complications, and our initial observation is that by performing broad mastoidectomy with posterior attic and facial recess exposure, recurrence of acute mastoiditis can be prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0
3

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 30 publications
0
7
0
3
Order By: Relevance
“…S. pneumoniae was rare (3.4%). Other studies have reported a very high prevalence of S. pneumoniae infection in AM (21–77%) (14–16) and have declared it to be the predominant pathogen. An explanation for the difference to other studies might be the pneumococcal vaccination, which was introduced and recommended by the Standing Committee on Vaccination in Germany in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…S. pneumoniae was rare (3.4%). Other studies have reported a very high prevalence of S. pneumoniae infection in AM (21–77%) (14–16) and have declared it to be the predominant pathogen. An explanation for the difference to other studies might be the pneumococcal vaccination, which was introduced and recommended by the Standing Committee on Vaccination in Germany in 2006.…”
Section: Discussionmentioning
confidence: 99%
“…17 Based on a recent systematic review of pediatric acute mastoiditis management, nearly 75% of the patients with uncomplicated cases were cured without surgical therapy; however, myringotomy with or without tube placement achieved a 94% cure rate. 18 For complicated cases, treatment may involve intravenous antibiotic therapy with or without myringotomy, 6 mastoidectomy (if the infection is not controlled after 48 hours of intravenous antibiotics), 19 and craniotomy (in severe cases with intracranial complications). 20 According to the systematic review by Anne et al, 18 mastoidectomy achieved a 100% cure rate, whether performed alone or after less invasive procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Em quadros persistentes é adotado a ingestão de fármacos com incisão e drenagem de abscesso sub-periosteal. Em último caso, é realizado o tratamento farmacológico com mastoidectomia/revisão de mastoidectomia (MIERZWIŃSKI et al, 2019).…”
Section: Lista De Abreviaturasunclassified